UPAYA MENINGKATKAN KREATIVITAS BELAJAR MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA PADA PESERTA DIDIK KELAS X SMA NEGERI 7 PONTIANAK - Putri, Kurnia Amelia; Asrori, Muhammad; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Learning creativity is also described as problem-solving ability because students are trained to think in achieving their goals. The general problem in this study is "How to increase student learning creativity with sociodrama techniques in class X SMA Negeri 7 Pontianak in 2020? The method in this study is descriptive method. Before being given the sociodrama technique 53% in the medium category and after being given the sociodrama technique it was 86% in the high category. So it can be concluded that the sociodrama technique to improve the learning creativity of students in class X SMA Negeri 7 Pontianak is good. Suggestions (1) Guidance and Counseling Teachers are expected to improve the process of implementing the Sociodrama Technique by implementing the Sociodrama Technique two or three times in one semester. (2) For students are expected to be more active (3) For researchers are expected to be able to make students explore the roles played by students who take part in Sociodrama Engineering activities.